Progress of Binder Structures in Silicon-Based Anodes for Advanced Lithium-Ion Batteries: A Mini Review - Zhu, Wenqiang; Zhou, Junjian; Xiang, Shuang; Bian, Xueting; Yin, Jiang; Jiang, Jianhong; Yang, Lishan (Frontiers in Chemistry, 2021)
Silicon is considered as one of the most promising anode materials for the next-generation lithium-ion batteries, owing to its high theoretical specific capacity, safety, and high natural abundance. However, the commercial application of silicon anodes is hindered by its huge volume expansions, poor conductivity and low coulombic efficiency. The binders for the anode manufacture play an important role of binding active materials, current collectors and conductive agents, and the binder structure can significantly affect the mechanical durability, adhesion, ionic/electronic conductivities of the silicon anodes. Especially, cross-linked binders are effective at alleviating the volume expansions of silicon anodes along with excellent electrochemical performances. This work comprehensively summarizes the mechanisms how various binders and their polymer structures influence the performances of the silicon anodes, the limitations and prospects of different binder polymers are also discussed for designing new binders to facilitate silicon anodes with high electrochemical activity and long-term stability. This mini review can offer researchers a summary about recent research achievements and guide to address silicon-based anode issues associated with mechanical properties and electrochemical performances.